Relationships Among HIV/AIDS Orphanhood, Stigma, and Symptoms of Anxiety and Depression in South African Youth: A Longitudinal Investigation Using a Path Analysis Framework - Boyes, Mark; Cluver, L. (Sage Publications, 2013)
Cross-sectional research has demonstrated that HIV/AIDS orphanhood is associated with anxiety and depression and that HIV/AIDS-related stigma is a risk factor for these outcomes. This study used a longitudinal data set to determine whether relationships between HIV/AIDS orphanhood and anxiety/depression scores (measured at 4-year follow-up) operate indirectly via perceived stigma. Youths from poor communities around Cape Town were interviewed in 2005 (n = 1,025) and followed up in 2009 (n = 723). At baseline, HIV/AIDS-orphaned youth reported significantly higher stigma and depression scores than youth not orphaned by HIV/AIDS. At follow-up, HIV/AIDS-orphaned youth reported significantly higher stigma, anxiety, and depression scores. However, HIV/AIDS orphanhood was not directly associated with anxiety or depression. Instead, significant indirect effects (operating through perceived stigma) were obtained for both assessment periods. Results demonstrate that stigma persists across time and appears to mediate relationships between HIV/AIDS orphanhood and psychological distress. Interventions aiming to reduce stigma may help promote the mental health of HIV/AIDS-orphaned youth.